Religious Violence in the Indonesian Democratic Era - J., Hasse; Hidayati, Mega (Pascasarjana IAIN Pontianak, 2018)
The Indonesian democratic era has provided hope for the growth of mutual social practices established upon diversity of ethnicity, religions, race, and inter-group relations. Yet, in the last decade, various forms of violence were often carried out on behalf of religion instead. These acts of violence were not only physical but also psychological (cultural), in the forms of discrimination, abuse, expulsion, insult, and threat. The Ahmadiyya and Shia cases, for instance, provide an outlook regarding the prevalence of violence within social practices in the community in response to differences. Why does such violence remain to occur in Indonesia? The work finds that, aside from a ‘failed understanding of religious texts’, excessive truth claim also triggers acts of religious violence in the current era of Indonesian democracy. It is of utmost importance that people’s understanding and interpretation of differences be set straight so that any response to differences can be considered as an embryo of national power that serves as an instrument employed for uniting the people of this nation instead of disuniting them. It is also strongly indicated by the work that religious violence may be avoided by changing the understanding of the meaning of differences.